PENGEMBANGAN PERANGKAT MODEL PEMBELAJARAN PEMEROLEHAN KONSEP (CONCEPT ATTAINMENT) UNTUK MENUNTASKAN HASIL BELAJAR SISWA PADA PELAJARAN FISIKA DI SMP - Ilmi, Miftakhul (Religi, 2012)
Abstract The aims of this research was to develop an concept attainment model oriented physics learning package which had criteria in validity, difficully level, readability of student’s book, other aims were to describe the teaching and learning process, student activity, student response, and student achievement. The physics learning package has been implemented using one group pretest posttest design in student of grade VIII B ( 35 Students) at SMP Unggulan Amanatul Ummah Surabaya. The analized data revealed that: the developed learning package a good category and could be used with a few revision in certain aspects. The percentage of difficully level of student’s book were 24,0 % respectively. The percentage of readability student’s book were 50,8 % respectively. The lesson plan was also good implemented. The results of students achievement had reached more than 70 classically completeness. Based on those findings, it could be concluded that concept attainment model oriented on physisc learning package of rays refraction main topic could be well implemented succesfully instudent of grade VIII B (35 Students) at SMP Unggulan Amanatul Ummah Surabaya and it could achieve the teaching learning of students achievement. Keywords : The Development Of Learning Package, The Concept Attainment Model.